The wedding - Coovadia, Imraan 1970- (Picador USA, 2001)
Ismet Nassim, a clerk from Bombay, impulsively marries a beautiful women he saw standing next to a village well. Ismet soon learns that even after a move to South Africa, his marriage will not be a happy one.
Keywords: East Indians -- South Africa -- Fiction; Weddings -- Fiction; Südafrika (Staat); Bombay (India) -- Fiction; Durban (South Africa) -- Fiction; South Africa -- Fiction; Domestic fiction; Humorous fiction